2022
DOI: 10.3389/fpsyt.2022.932306
|View full text |Cite
|
Sign up to set email alerts
|

Integrated hepatitis C treatment is associated with improved retention and success in outpatient treatment for opioid use disorder at a private clinic

Abstract: BackgroundDirect acting antiretrovirals (DAA) are effective for individuals who are infected with chronic hepatitis C virus (HCV), yet many people go without access to these lifesaving treatments.Materials and methodsWe conducted a non-randomized study evaluating treatment data for patients in outpatient treatment for opioid use disorder (OUD) at a private clinic. Patients who were HCV-positive, had been in OUD treatment for at least 4 weeks, and engaged in integrated HCV treatment with DAA (co-located within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These observations underscore the potential ineffectiveness of audio-only solutions when evaluating people with OUD. Participants indicated that codispensing HCV medications and methadone increases HCV medication adherence and adds value by potentiating improvements in OUD recovery [ 38 ]. New York State regulations and OTP administrators permitted the codispensing of HCV medications and methadone.…”
Section: Discussionmentioning
confidence: 99%
“…These observations underscore the potential ineffectiveness of audio-only solutions when evaluating people with OUD. Participants indicated that codispensing HCV medications and methadone increases HCV medication adherence and adds value by potentiating improvements in OUD recovery [ 38 ]. New York State regulations and OTP administrators permitted the codispensing of HCV medications and methadone.…”
Section: Discussionmentioning
confidence: 99%
“…These observations underscore the potential ineffectiveness of audio-only solutions when evaluating people with OUD. Participants indicated that co-dispensing HCV medications and methadone increases HCV medication adherence and adds value by potentiating improvements in OUD recovery [34]. New York State regulations and OTP administrators permitted co-dispensing of HCV medications and methadone.…”
Section: Participant Meanings and Practical Advicementioning
confidence: 99%